If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y(8 + x) + -3 + 9 = 23 (8 * 6y + x * 6y) + -3 + 9 = 23 Reorder the terms: (6xy + 48y) + -3 + 9 = 23 (6xy + 48y) + -3 + 9 = 23 Reorder the terms: -3 + 9 + 6xy + 48y = 23 Combine like terms: -3 + 9 = 6 6 + 6xy + 48y = 23 Solving 6 + 6xy + 48y = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 6xy + -6 + 48y = 23 + -6 Reorder the terms: 6 + -6 + 6xy + 48y = 23 + -6 Combine like terms: 6 + -6 = 0 0 + 6xy + 48y = 23 + -6 6xy + 48y = 23 + -6 Combine like terms: 23 + -6 = 17 6xy + 48y = 17 Add '-48y' to each side of the equation. 6xy + 48y + -48y = 17 + -48y Combine like terms: 48y + -48y = 0 6xy + 0 = 17 + -48y 6xy = 17 + -48y Divide each side by '6y'. x = 2.833333333y-1 + -8 Simplifying x = 2.833333333y-1 + -8 Reorder the terms: x = -8 + 2.833333333y-1
| 4x+7=29+2x | | Y=-.04x(x-24) | | 5.7k-3.78k=25.8192-1.34k | | [3/10][-11/12] | | 98=2L+(26) | | 6(3v-7)-2=0 | | 6-3+4x+1=4x+4 | | 102/3 | | 2/3xy-z=a | | 2(98)=2(26) | | 15/x=x/3 | | 8a+1+1=48 | | 7-r=-23 | | 5y-31=3y+3 | | Y=0.5x(x-3) | | X+8=14-x | | 9+2b-8=15 | | 3(4-3x)=3(3x+5) | | 35=t-13 | | 7m=-11 | | 78x+28=180 | | 6-3+4x+1=4x+1 | | secx=tanx-1 | | 2x-12=-3x+8 | | 10n+4+3=67 | | 3(3x-5x)+2=-8 | | 3+y=27 | | 9d/12-d/12= | | -10m-7+3-4m= | | 14m+19=28m+12 | | dx+dx=30 | | Y+6=52 |